Collagen-functionalized electrospun smooth and porous polymeric scaffolds for the development of human skin-equivalent. Issue 45 (15th July 2020) - Ravindran Girija, Aswathy; Palaninathan, Vivekanandan; Strudwick, Xanthe; Balasubramanian, Sivakumar; Dasappan Nair, Sakthikumar; Cowin, Allison J.
Abstract : Collagen-functionalized electrospun smooth and porous poly(l -lactide) scaffolds supporting keratinocytes and fibroblasts as a potential model to serve as self-organized skin substitute. Abstract : Electrospun polymer fibers have garnered substantial importance in regenerative medicine owing to their intrinsic 3D topography, extracellular matrix microenvironment, biochemical flexibility, and mechanical support. In particular, a material's nano-topography can have a significant effect on cellular responses, including adhesion, proliferation, differentiation, and migration. In this study, poly(l -lactic acid) (PLLA), a biodegradable polymer with excellent biocompatibility was electrospun into fibers with either smooth or porous topologies. The scaffolds were further modified and biofunctionalized with 0.01% and 0.1% collagen to enhance bioactivity and improve cellular interactions. Human keratinocytes (HaCaTs) and fibroblasts (human foreskin fibroblasts-HFF) were cultured on the scaffolds using a modified co-culture technique, where keratinocytes were grown on the dorsal plane for 5 days, followed by flipping, seeding with fibroblasts on the ventral plane and culturing for a further 5 days. Following this, cellular adhesion of the skin cells on both the unmodified and collagen-modified scaffolds (smooth and porous) was performed using scanning electron microscopy (SEM) and immunofluorescence. Distinct outcomes were observed with the unmodified smooth scaffolds showing superior cell adhesion than the porous scaffolds. Modification of the porous and smooth scaffolds with 0.1% collagen enhanced the adhesion and migration of both keratinocytes and fibroblasts to these scaffolds. Further, the collagen-modified scaffolds (both porous and smooth) produced confluent and uniform epidermal sheets of keratinocytes on one plane with healthy fibroblasts populated within the scaffolds. Thus, presenting a vast potential to serve as a self-organized skin substitute this may be a promising biomaterial for development as a dressing for patients suffering from wounds.